Community acquired versus hospital acquired acute kidney injury; causes and outcome - Khan, Farah Gul; Awan, Safia; Namran, Sidra; Baqir, Syed Mujtaba (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate causes of community-acquired and hospital-acquired acute kidney injury and the factors associated with increased inpatient mortality. Method: The observational prospective study was conducted at the Aga Khan University Hospital, Karachi, from September 2018 to March 2019, and comprised patients having acute kidney injury either at the time of admission in group A or developed it after 48 hours of hospital stay in group B. The patients were followed up for 12 weeks and outcomes were categorised as recovered, developed chronic kidney disease, died or remained dialysis-dependent. Data was analysed using SPSS 19. Results: Of the 400 patients, 347(86.8%) were in group A; 190(54.8%) males and 157(45.2%) females with an overall mean age of 57.2±17.0 years. The remaining 53(13.3%) were in group B; 31(58.5%) males and 22(41.5%) females with an overall mean age of 58.5±16.3 years. Urinary tract infection 105(30.3%) was the most frequent cause in group A, followed by volume depletion 73(21%). The causes in group B were multiple, with nephrotoxic antibiotics vancomycin 21(39.6%) and polymyxin 20(37.7%) being the most common. At 12 weeks, 224(56%) patients recovered, 55(13.8%) died, 82(20.5%) and 38(9.5%) developed new onset and progressive chronic kidney disease, respectively, and 1(0.25%) patient remained dialysis-dependent. Chronic liver disease, renin angiotensin system inhibitors, infection, shock, invasive ventilation and increasing length of stay were associated with increased inpatient mortality (p<0.05). Conclusion: Acute kidney injury was largely community-acquired, and infection was the leading cause with better outcome in contrast to hospital-acquired acute kidney injury which was mostly multifactorial.